Livable City/Unequal City: The Politics of Policy-Making in a « Creative » Boomtown - Eugene J. McCann (Revue Interventions Économiques)
There is a tendency in contemporary North American urban policy-making to uncritically connect specific ideals of urban ‘livability’ with efforts to cater to the whims of the so-called ‘Creative Class.’ The paper engages with this tendency through an analysis of the politics of urban policy-making in Austin, Texas – a place regarded as an exemplar of ‘livability’ and ‘creativity.’ With reference to the Austin case, the paper identifies and describes two related spatial frames that underpin the ‘Creative Class’ thesis and its relationship to a certain conception of urban livability – an idealization of the vibrant urban neighbourhood and a moral geography of competing ‘livable’ and ‘creative’ cities. The paper then addresses the question of inequality and its relationship to policies aimed at nurturing, attracting, and retaining the ‘Creative Class.’ This is done through a discussion of Austin’s experience of rising economic inequality and declining housing affordability just as the city became ‘creative’ and ‘livable.’ The paper’s core argument is that policy-makers must acknowledge and address the inequality that seems to result from the implementation of narrow ‘livability’ and ‘creativity’ policies and that advocates of the ‘Creative Class’ thesis must address, with more than hand-wringing and platitudes, evidence that ‘creative cities’ are becoming increasingly less livable for most people.